The Natural resource curse - Bardorj, Bolortsetseg (KDI School, 2011)
Natural resource rich countries have the tendency to grow less than resource poor countries. Some mineral rich countries in Africa such as Nigeria, Sudan, Angola and the Congo are still less developed: their people live with a low standard of life and are still suffering from poverty. Mean while, other East Asian mineral resource poor countries such as Hong Kong, Thailand, South Korea and Japan are developing rapidly. They have achieved western-level standards of live. The reasons of lover development are the negative impacts of the natural resource curse and a lack of management for mitigating it. The study undertakes empirical evidences to explore the impacts of the natural resource curse. Within an analytical framework based on a literature review on the natural resource curse, the study provides further empirical support to the impacts of the natural resource curse in Mongolia using technical data. Based on a Chilean experiment on how to combat against the natural resource curse, the findings of the study state some suggestions on mitigating negative effects.
Thesis(Master) --KDI School:Master of Public Policy,2011